Fecal microbiota transplantation treatment of autoimmune-mediated type 1 diabetes mellitus - He, Lina; Chen, Rongping; Zhang, Bangzhou; Zhang, Shuo; Khan, Barkat Ali; Zhu, Dan; Wu, Zezhen; Xiao, Chuanxing; Chen, Baolong; Chen, Fengwu; Hou, Kaijian (Frontiers in Immunology, 2022)
Type 1 Diabetes Mellitus (T1DM) is an autoimmune-mediated disease characterized by reduced or absolute lack of insulin secretion and often associated with a range of vascular and neurological complications, for which there is a lack of effective treatment other than lifestyle interventions and pharmacological treatments such as insulin injections. Studies have shown that the gut microbiota is involved in mediating the onset and development of many fecal and extrafecal diseases, including autoimmune type 1 diabetes. In recent years, many cases of gut microbiota transplantation for intra- and extra-fecal diseases have been reported worldwide, and this approach has been shown safe and effective. Here, we conducted an experimental treatment study in two adolescent patients diagnosed with autoimmune type 1 diabetes for one year. Patients received two to three normal fecal microbiota transplants (FMT) and were followed for 30 weeks. Clinical outcomes were measured, including biochemical indices, medication regimen, and dosage adjustment. Fecal microbiota macrogenomic sequencing after transplantation provides a reference for more reasonable and effective microbiota transplantation protocols to treat autoimmune type 1 diabetes. Our results suggest that FMT is an effective treatment for autoimmune type 1 diabetes.